PENGARUH ENVIRONMENTAL PERFORMANCE TERHADAP ECONOMIC PERFORMANCE - Titisari, Kartika Hendra; Alviana, Khara (Jurnal Akuntansi dan Keuangan Indonesia, 2012)
The purpose of this study is to examine the impact of environmental performance on economic performance current year and the after year. This study is based on a longitudinal empirical applied research. Through a purposive sampling technique, 28 public companies which participated in the PROPER program from 2007-2009 were included in the research. The results of hypothesis testing shows envirnoment performance affect the economic performance of the current year and no effect on the economic performance after year. So for companies particularly vulnerable to environmental public company in Indonesia who want to improve economic performance in the current year should also improve the environmental performance to gain the trust of the community. The next level of corporate environmental performance is valuable information that deserves consideration as one of the criteria for rational investment decisions by investors.